PROGNOSTIC IMPACT OF NEUROPILIN-1 EXPRESSION IN EGYPTIAN CHILDREN WITH B-LINEAGE ACUTE LYMPHOBLASTIC LEUKEMIA - adel abd elhaleim hagag; Nahla A Nosair (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract: Background: Neuropilins are transmembrane glycoproteins that act as receptors for vascular endothelial growth factors and are involved in the process of tumor angiogenesis. Objective: The aim of this work was to study the prognostic value of neuropilin-1 (NRP-1) expression in children with B-lineage ALL. Subjects and methods: This study was conducted on fifty children with newly diagnosed B-lineage ALL who were admitted in Oncology Unit, Pediatric Department, Tanta University Hospitals in the period from August 2010 to March 2014 including 32 males and 18 females with their ages ranged from 3-17 years and mean value of 9 ± 3.5 years. Twenty healthy age and sex matched children serving as a control group was also included in this study. Patients were subjected to history taking, clinical examination and laboratory investigations including; complete blood count, serum LDH levels, bone marrow aspiration, cytochemistry, immunophenotyping and estimation of nuropilin-1 expression on blast cells by flow cytometry. Results: The present study revealed highly significant differences in NRP-1 expression between patients with B-lineage ALL and controls. The highest levels of NRP-1 expression were noted in pre-B ALL (74.04%) followed by early pre-B (23.55%) and lastly mature B-ALL (12.06%) with significant difference between the three subtypes. NRP-1 expression was significantly associated with higher white blood cells count, bone marrow blasts percentage and serum lactate dehydrogenase levels at diagnosis and there were significantly higher levels of NRP-1 expression on BM blasts at diagnosis in patients who subsequently relapsed or died later on during the period of follow up compared to those who achieved and maintained complete remission. Also, patients with higher NRP-1 expression had significantly shorter overall survival (OS) and disease free survival (DFS) than patients with low NRP-1 expression. Conclusion: Our findings suggest that neuropilin-1 has bad prognostic impact in children with B-lineage ALL and so we can recommend the incorporation of NRP-1 as a prognostic marker in children with B-lineage ALL to offer a chance for intensive therapeutic intervention in patients designated as having poor prognosis.